THE ROLE OF BALINESE HINDU TRADITION IN PROMOTINGRELIGIOUS MODERATION IN SEMARANG - Putrawan, I Nyoman Alit; Subagia, I Nyoman; Masrur, Masrur; Gunarta, I Ketut; Putra, I Gede Desi Diana (PT. Anagata Sembagi Education, 2025)
Religious moderation is a crucial element in maintaining social harmony in Indonesia, especially in cities with religious diversity such as Semarang. Balinese Hindu traditions play a significant role in strengthening the values of tolerance and mutual respect through various cultural and religious practices. This study analyzes how Balinese Hindu traditions, including the Melasti ceremony and the Nyepi celebration, contribute to religious moderation in Semarang. This study uses a narrative descriptive approach with the aim of understanding in depth how Balinese Hindu traditions contribute to promoting religious moderation in Semarang. The data collection method was carried out through direct observation,in-depth interview, And Documentation analysis. Observations were conducted by observing religious practices and cultural activities involving the Balinese Hindu community as well as the participation of non-Hindus in religious events. Interviews were conducted with religious leaders, community leaders, and individuals involved in interfaith activities to gain a broader perspective on social interactions and the application of religious moderation values. Documentation analysis included literature studies from academic journals, official reports, and relevant statistical data to strengthen the research findings. The results of the study indicate that interfaith interactions in the Balinese Hindu tradition can increase understanding and respect between religious communities, as well as strengthen social harmony. In addition, cultural festivals and interfaith activities play an important role in building dialogue and cooperation between communities. These findings confirm that the Balinese Hindu tradition not only functions as a cultural identity, but also as an effective means of promoting religious moderation in a multicultural environment.